Methodological foundations of the formation of environmental awareness in the practice of teaching linguistic disciplines - Butkevich, Yuliya (Journal of the Belarusian State University. Ecology, 2024)
The integration of ecological educational components into the practice of teaching foreign languages opens wide opportunities for the formation of students’ environmental consciousness. This article discusses the methodological foundations that ensure this process. First of all, the principles underlying the inclusion of ecological topics in linguistic disciplines and determining the effective integration of ecological content and language teaching objectives based on interdisciplinary approaches, pedagogical theories and practical strategies are conceptualized. In addition, the methodological foundations of the most effective research practices in language teaching and environmental education are highlighted, and new trends and innovations in both fields are characterized. The article elaborates on different pedagogical models such as Project Based Learning (PBL), Content and Language Integrated Learning (CLIL), Task Based Language Teaching (TBLT), Flipped classroom and reveals the mechanisms that promote the simultaneous development of environmental awareness, language competence and critical thinking skills. Special attention is paid to demonstrating the key role of educators in creating meaningful learning experiences that promote environmental stewardship and intercultural understanding. The article emphasizes the importance of creating an educational environment in which students are encouraged to learn about environmental topics through authentic language use, thereby developing a deeper understanding of environmental issues. By illustrating the methodological framework through the lens of specific English language teaching methods, the article reveals practical strategies for seamlessly integrating language education with the formation of environmental awareness. Demonstrating the value of innovative teaching methods and experiential learning opportunities, the article shows how language teachers can effectively weave environmental themes into their curricula, empowering students to become not only informed but conscious advocates of sustainable development strategies and environmental justice. This article reveals a number of possibilities that arise from combining language education and the process of building environmental awareness. It substantiates the effectiveness of adopting a holistic approach to learning that transcends disciplinary boundaries and equips students with the linguistic, cognitive and socio-environmental competencies necessary for self-actualization in an increasingly dynamic and interconnected world.
Keywords: environmental awareness; teaching methodology; environmental education; interdisciplinary approaches; project-based learning; content-language integrated learning; task-based language teaching; flipped classroom